Factibilidad del proceso de atención de enfermería nanda nic noc en los pacientes de las Áreas Críticas del Hospital Teófilo Dávila. Machala 2014. - Carpio Rosales, Maria Alexandra (2014)
The following research I perform as prior to obtaining the bachelor's degree in nursing work, part of the interest of the observation process management of nursing care in Teofilo Davila process hospital that has been unnoticed and unimportant by staff and today the accreditation of hospitals the need of the fulfillment of the indicators , which is why the following study was performed overall objective Determine the feasibility of the process of nursing NANDA NIC NOC patients in critical areas of the hospital Teofilo Davila. Machala 2014 .